Floristic diversity and economic importance of wild relatives of cultivated plants in Uzbekistan (Central Asia) - OZODBEK S. ABDURAIMOV; AZIZBEK V. MAXMUDOV; IGOR KOVALENKO; AKMAL L. ALLAMUROTOV; BEKZOD J. MAVLANOV; SARIBAEVA U. SHAKHNOZA; ODILBEK T. MAMATKASIMOV (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Abduraimov OS, Maxmudov AV, Kovalenko I, Allamurotov AL, Mavlanov BJ, Shakhnoza SU, Mamatkasimov OT. 2023. Floristic diversity and economic importance of wild relatives of cultivated plants in Uzbekistan (Central Asia). Biodiversitas 24: 1668-1675. The countries of Central Asia are considered one of the Centers of origin of cultivated plants and their wild relatives. Indigenous people have used these plants for several centuries. Our study was carried out in 2020-2022 in different biogeographical regions of Uzbekistan. Data from field studies and literature showed that in the flora of Uzbekistan, there are 24 families, including 202 species belonging to 102 genera. In the current investigation, an attempt has been made to document the floristic diversity and economic importance of wild relatives of cultivated plants in Uzbekistan. Wild Relatives of Cultivated Plants (WRCP) and cultivated species form an integral part of the genetic resources of plants that determine the food security of the assessment and are subject to conservation at the international level. The WRCP includes species of natural flora that are evolutionarily close to cultivated plants, are included in the same genus, and are potentially suitable for introducing into culture for creating or improving cultivated plant varieties. Most wild relatives of crop plants worldwide need to be addressed and utilized, recognizing their real potential. Humans have been using these plants for several centuries. In recent years, the demand for food has been increasing. Our study suggests making them possible to use these varieties of plants regularly.